Pengaruh Penguasaan Kosakata dan Tata Bahasa Indonesia Terhadap Kemampuan Menulis Eksposisi Siswa Kelas X SMA Negeri Se Kota Yogyakarta - Pasaribu, Christin; Rokmah, Rokmah; Mardiansyah, Mardiansyah; Hilaliyah, Tatu (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to: (1) determine whether or not there is an influence of vocabulary mastery on the exposition writing ability of class X SMA Negeri Se-Kota Yogyakarta (2) determine whether or not there is an influence of mastery of Indonesian grammar on the ability to write expositions of class X SMA Negeri Se-Kota Yogyakarta, and (3) determine whether or not there is an influence of mastery of Indonesian vocabulary and grammar on the ability to write expositions of class This research is ex-post facto research. The research subjects were students class X SMA Negeri Se-Kota Yogyakarta. Sampling used a stratified random sampling technique with a total of 345 students taken. Data collection was carried out using ability tests including vocabulary, grammar and expository writing. Data analysis uses product moment correlation analysis techniques and multiple linear regression analysis. The level of error in the analysis results is determined at 5%. The results of the research show that: (1) there is a positive and significant influence of vocabulary mastery on expository writing ability class X student of SMA Negeri se-Kota Yogyakarta with a calculated r value of 0.164, r table of 0.098, relative contribution of 30.29% and effective contribution of 1.82%; (2) there is a positive and significant influence of mastery of Indonesian grammar on the exposition writing ability of class X student SMA Negeri se-Kota Yogyakarta which is indicated by the calculated r value of 0.221, r table of 0.098, relative contribution of 69.71% and effective contribution of 4.18%; (3) there is a positive and significant influence simultaneously on the mastery of Indonesian vocabulary and grammar on the exposition writing ability of class X student SMA Negeri se-Kota Yogyakarta indicated by an F value of 10.950, a regression coefficient (R) of 0.245, and a coefficient of determination (R2) of 0.060. This means that 6% of expository writing ability is influenced by mastery of vocabulary and grammar, while the remaining 94% is influenced by other factors not examined in this research.